Social networking: A matter of character? - Vieth, M.; Kommers, Piet (Inderscience Publishers, 2014)
Over the last couple of years, online social networks such as Facebook have tremendously grown in popularity, especially among students. The technological advancements proceed faster than the understanding of the psychological factors behind this development. While motivations and gratifications related to Facebook usage have been investigated thoroughly, this study additionally focuses on the influence of underlying personality factors. However, instead of the commonly used Big Five, the characteristics narcissism, shyness and loneliness are investigated among undergraduate and graduate students. The results indicate that a high score on narcissism causes a higher Facebook usage and that the sub construct uniqueness/entitlement is the most important. The results also indicate a negative influence of loneliness on Facebook usage, while shyness seems irrelevant.